2019
DOI: 10.1002/cbic.201900148
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biochemical Evaluation of an Artificial, Fluorescent Glucosinolate (GSL)

Abstract: The synthesis of the first example of a fluorescent glucosinolate (GSL)–BODIPY conjugate based on an azide‐containing artificial GSL precursor (GSL‐N3) is reported. Biochemical evaluation of the artificial GSLs revealed that the compounds are converted to the corresponding isothiocyanates in the presence of myrosinase. Furthermore, myrosinase‐catalyzed hydrolysis in the presence of plant specifier proteins yielded the expected alternative products, namely nitriles. The easy assembly of the fluorescent GSL–BODI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Camalexin, cyanogenic 4-OH-ICN metabolite, and indole glucosinolates are three classes of known tryptophan-derived defense metabolites. Among them, camalexin and 4-OH-ICN, produced through CYP71A12 and CYP71A13, were shown to act as specialized defense compounds against aphids and a variety of plant pathogens (Thomma et al, 1999;Bohman et al, 2004;Kettles et al, 2013;Glindemann et al, 2019;. Here, we demonstrated that defense compounds synthesized through CYP71A12-and CYP71A13dependent pathways are not protecting Arabidopsis from mite herbivory, Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Camalexin, cyanogenic 4-OH-ICN metabolite, and indole glucosinolates are three classes of known tryptophan-derived defense metabolites. Among them, camalexin and 4-OH-ICN, produced through CYP71A12 and CYP71A13, were shown to act as specialized defense compounds against aphids and a variety of plant pathogens (Thomma et al, 1999;Bohman et al, 2004;Kettles et al, 2013;Glindemann et al, 2019;. Here, we demonstrated that defense compounds synthesized through CYP71A12-and CYP71A13dependent pathways are not protecting Arabidopsis from mite herbivory, Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The copyright holder for this preprint this version posted February 3, 2021. ; https://doi.org/10.1101/2021.02.03.429630 doi: bioRxiv preprint al., 2014). CYP79B2 and CYP79B3 are required for the conversion of tryptophan to indole-3-acetaldoxime (IAOx) that is further processed by CYP71A13, CYP71A12, and CYP83B1 to initiate biosynthesis of camalexin, cyanogenic metabolite 4-OH-ICN and indole glucosinolate (IG) defense compounds, respectively (Zhao et al, 2002;Vik et al, 2018;Glindemann et al, 2019;. 3-Indolylmethyl glucosinolate (I3M) is a parental indole glucosinolate that is further hydroxylated by cytochromes P450 of the CYP81 family and methylated by IG methyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Retrosynthetic analysis for nitrabirine (5) Subsequent substitution of the chloride in the presence of sodium azide in dimethylformamide at 80°C yielded the known 16 azide 16 in 83% yield. 17 Reduction of the β-oxo group of 16 in the presence of sodium borohydride in ethanol gave the known 18 secondary alcohols 15 and 15' in a 1:1 mixture of the diastereomers. Finally, the reduction of the azide moieties of 15 and 15' to the amino groups in the presence of Zn/NH4Cl in ethanol:water/3:1 19 followed by spontaneous ring closure to the δ-spiro lactame at 80°C led to a 2:1-mixture of the known 11 diastereomers 14 and 14', which could be separated by flash column chromatography through silica gel and were obtained in 35% and 17%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Camalexin, cyanogenic 4-OH-ICN metabolite, and indole glucosinolates are three classes of known tryptophan-derived defense metabolites. Among them, camalexin and 4-OH-ICN, produced through CYP71A12 and CYP71A13, were shown to act as specialized defense compounds against aphids and a variety of plant pathogens (Thomma et al, 1999; Bohman et al, 2004; Ferrari et al, 2007; Sanchez-Vallet et al, 2010; Schlaeppi et al, 2010; Kettles et al, 2013; Glindemann et al, 2019; Pastorczyk et al, 2020). Here, we demonstrated that defense compounds synthesized through CYP71A12- and CYP71A13-dependent pathways are not protecting Arabidopsis from mite herbivory, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic glucosinolates are not effective against mites, however, mite fitness increases on the cyp79b2 cyp79b3 mutant plants, indicating that the Trp-derived secondary metabolite(s) restrict mite herbivory (Zhurov et al, 2014). CYP79B2 and CYP79B3 are required for the conversion of tryptophan to indole-3-acetaldoxime (IAOx) that is further processed by CYP71A13, CYP71A12, and CYP83B1 to initiate biosynthesis of camalexin, cyanogenic metabolite 4-OH-ICN and indole glucosinolate (IG) defense compounds, respectively (Zhao et al, 2002; Sanchez-Vallet et al, 2010; Rajniak et al, 2015; Vik et al, 2018; Glindemann et al, 2019; Pastorczyk et al, 2020). 3-Indolylmethyl glucosinolate (I3M) is a parental indole glucosinolate that is further hydroxylated by cytochromes P450 of the CYP81 family and methylated by IG methyltransferases.…”
Section: Introductionmentioning
confidence: 99%